The Hadassah Jewish family book of health and wellness - Berman, Robin E. (Jossey-Bass, 2006)
The Hadassah Jewish Family Book of Health and Wellness, written in collaboration with Hadassah: The Women’s Zionist Organization of America, known throughout the world for its leadership as a major force in health research and education, provides a much-needed resource and guide to physical health and spiritual issues that are of concern to Jewish families